A265 SERIAL FECAL MICROBIOTA TRANSPLANT PLUS FIDAXOMICIN IN THE TREATMENT OF SEVERE OR FULMINANT CLOSTRIDIOIDES DIFFICILE INFECTION. (26th February 2020) - Russell, L; Roach, B; Yang, D Y; Wang, C; Wine, E; Saxinger, L; Wong, K; Kao, D H
Abstract: Background: Severe and fulminant Clostridioides Difficile infection(CDI) is associated with increased mortality and morbidity. Current guidelines recommend high dose vancomycin with metronidazole for treatment. Surgery is a high risk for patients failing medical therapy partly due to multiple comorbidities. Emerging evidence suggests efficacy of sequential fecal microbiota transplantation(FMT) by colonoscopy combined with vancomycin in patients failing maximal medical therapy. Fidaxomicin is non-inferior to vancomycin in treating CDI; however, it has not been studied in severe/fulminant cases. It is not known if FMT by enema combined with fidaxomicin is efficacious and safe in this patient population. Aims: This single center, prospective, open-label pilot study aimed to determine the efficacy and safety of combined sequential FMT by enema plus fidaxomicin in severe or fulminant CDI not responding to maximal medical therapy. Primary outcome was resolution of diarrhea 2 weeks following final FMT. Secondary outcomes were resolution of diarrhea 8 weeks following final FMT, safety of proposed treatment protocol and colectomy rate. Methods: Consecutive patients with severe or fulminant CDI, who fulfilled study inclusion criteria were recruited. Sequential cycles of FMT, administered by enema daily over three days(720cc followed by 360cc and 180cc), plus fidaxomicin 200mg PO BID were given. Clinical symptoms and inflammatory markers were monitored during the study and subsequent cycles of FMT were administered when clinical or biochemical improvement plateaued. A final FMT was administered with CDI resolution. Results: A total of three patients were enrolled between Jan 22 to Aug 8, 2019, shown in Table 1. One patient had fulminant CDI due to shock, and the others had severe CDI. All had severe pseudomembranous colitis seen on endoscopy at enrollment. Two of three patients reached both primary and secondary outcomes with 2 FMT cycles. The only patient who did not reach the primary was successfully managed with long term vancomycin suppression. This patient had failed multiple FMTs prior to enrollment. There were no adverse events noted and no colectomy was required during this study. Conclusions: This pilot study is the first to demonstrate efficacy and safety of combined sequential FMT by enema and fidaxomicin in treating severe or fulminant CDI patients. An adequately powered study is required to validate these findings. Funding Agencies: CIHRAlberta Health Services, University of Alberta Hospital Foundation